A Double-Blinded, Randomized, Placebo-Controlled Sub-Dissociative Dose Ketamine Pilot Study in the Treatment of Acute Depression and Suicidality in a Military Emergency Department Setting. Issue 10 (1st October 2016) - Burger, John; Capobianco, Marc; Lovern, Robert; Boche, Ben; Ross, Elliot; Darracq, Michael A.; McLay, Robert
ABSTRACT: Background: Rates of completed suicide in the military have increased. Options are limited for acute relief of depression and suicidal ideation. Traditional treatments' effects take weeks to months. A novel, rapid, therapeutic target has emerged with the N -methyl-D-aspartate antagonist ketamine. Previous studies suggest that a single dose of intravenous (IV) ketamine rapidly alleviates depression and suicidality. Methods: In this proof of concept study, an active duty convenience sample population presenting to the emergency department (ED) meeting criteria for inpatient psychiatric admission as a result of depression and suicidal thinking were randomized to receive either a subdissociative dose (0.2 mg/kg) of IV ketamine or equivalent volume of normal saline (placebo). Subjects were evaluated for symptoms throughout a 4-hour ED course, at hospital discharge, and 2 weeks postdischarge. Results: Methodological problems limited analyzable data to 10 subjects. Two of three who received ketamine experienced dramatic decreases in suicidality and hopelessness within 40 minutes. No such improvements were seen in any of seven controls over the 4-hour observation in the ED. At discharge from the hospital, there was no clinically significant difference. No subjects described adverse symptoms. Conclusion: Despite methodology difficulties noted in this pilot study, there was statistical improvement in intervention group versus controls.